A decision-theoretic model of asset price fluctuations - Alexander Ludwig; Alexander Zimper (Verein für Socialpolitik, 2010)
Based on the psychological interpretation of conditional non-additive probability measures arising in Choquet expected utility theory we introduce a behavioral model of asset price fluctuations. In this model naive agents are prone to a confirmatory bias in the interpretation of new information about economic fundamentals. As a conceptual advantage over rational expectations asset pricing models our formal approach gives rise to model-endogenous concepts of overpricing and underpricing. As another interesting feature our model generates equilibrium price patterns that reflect underreaction of asset prices with respect to one period good news as well as overreaction with respect to several periods of good news. These empirical phenomena have received signicant attention in the behavioral finance literature. In contrast to our approach, however, previous formal explanations have not been derived from decision-theoretic first principles but were rather ad hoc.
Keywords: C62; D81; G12; 330; Choquet Expected Utility Theory; Portfolio Choice; Asset Pricing Puzzles